Formation of microelement composition of soils of Stavropol krai under the influence of waterlogging processes - T. V. Degtyareva (Наука. Инновации. Технологии, 2025)
The object of the study was the hydromorphic soils of the Tashlyansky landscape of ravine forest-steppes, identified in the Stavropol Krai. The radial geochemical structure of differentiation of gross contents of Zn, Cu, Pb and Cd in the profile of meadow-chernozem soils formed under the influence of constant ground and seasonal surface moistening was studied. The features of lateral geochemi relation to the general lateral structure of migration of chemical elements, characteristic of the laid landscape-geochemical mesocatena within the Tashlyansky landscape, were also studied. The main methods were field and office analyses, analysis of scientific information on similar landscape-geochemical processes. The morphological characteristics and a number of physicochemical properties of meadow-chernozem soils have been established, which indicate the formation of differentiation in the soil profile by alkaline-acid conditions (there is a change from the neutral reaction of the environment in the humus horizon to a slightly alkaline one in the lower part of the soil profile) and oxidation-reduction conditions (there is a change from the oxidizing environment to a reducing gley environment). The radial differentiation structure of the total contents of Zn and Cu corresponds to the surface-accumulative distribution, which, together with the established statistically significant correlation coefficients with the humus content, indicates the fixation of Zn and Cu on the biogeochemical barrier as part of organomineral compounds. The radial differentiation structure of Pb and Cd is characterized by eluvial-illuvial distribution. The established correlation coefficients indirectly confirm the fixation of Pb and Cd as part of aluminosilicate clay minerals. Important phases-carriers of microelements in hydromorphic soils are oxides (hydroxides) of Fe and Mn, carbonates, easily soluble salts, which are visually determined in their profile. In the general picture of lateral differentiation of microelements along the landscape-geochemical mesocatena, meadow-chernozem soils act as low-contrast concentrators of Zn and Cu. More intensive radial migration of Pb and Cd from humus horizons in hydromorphic conditions affects the features of their lateral distribution along the landscape-geochemical mesocatena.